1963
DOI: 10.1128/jb.86.5.1101-1115.1963
|View full text |Cite
|
Sign up to set email alerts
|

MICROMORPHOLOGY OF DERMATOPHILUS CONGOLENSIS

Abstract: Gordon, Morris A. (Division of Laboratories and Research, New York State Department of Health, Albany), and Mercedes R. Edwards . Micromorphology of Dermatophilus congolensis . J. Bacteriol. 86: 1101–1115. 1963.—As seen in electron micrographs of thin sections, Dermatophilus congolensis is a holocarpic actinomycete that fragments, after formation of septa in several planes, into Sarcina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…Coccoid bodies with flagella can be recognised and the number of identified bodies was higher, especially with the scanning electron microscope. O u r findings, with only minor differences, are analogous to those which were described previously [7,11,14,15,16,23,261. Dermatophilosis [8,20] is almost invariably an animal skin infection, rarely transmitted to man.…”
Section: 860~supporting
confidence: 87%
“…Coccoid bodies with flagella can be recognised and the number of identified bodies was higher, especially with the scanning electron microscope. O u r findings, with only minor differences, are analogous to those which were described previously [7,11,14,15,16,23,261. Dermatophilosis [8,20] is almost invariably an animal skin infection, rarely transmitted to man.…”
Section: 860~supporting
confidence: 87%
“…In the present study, the capsule surrounding free cocci appeared to thicken with maturation, as compared to that on dividing structures. This was contrary to ROBERTS (1961) and GORDON and EDWARDS (1963) who reported that the hyphal capsule thickened during division.…”
Section: Abu-samra and Walton (1977)contrasting
confidence: 82%
“…Although previous studies on the morphology, mode of propagation and life cycle of Dermatophilus congolensis have been made (THOMPSON, 1954;THOMPSON and BISSET, 1957;AUSTWICK, 1958;ROBERTS, 1961;MB-MBRY, 1961;GORDON and EDWARDS, 1963;GORDON, 1964;RICHARD, RITCHIE and PIER, 1967;LUEDEMANN, 1968;GORDON, 1976), some aspects of the morphology of this organism remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mlicroscopic morphology. For descriptions and illustrations of sequential stages in the life cycle of D. congolensis, recent l)ublications (Roberts, 1961;Dean et al, 1961;and Gordon and Edwards, 1963) should be consulted. The lpresent studies resulted in observations similar to these and revealed no important differences in microscopic morphology among the putative three species.…”
Section: Downloaded Frommentioning
confidence: 99%